Large-scale path loss models and time dispersion in an outdoor line-of-sight environment for 5G wireless communications - Al-Samman, A. M. (Elsevier GmbH, 2016)
This paper presents path loss models and time dispersion parameters for different candidate frequencies above 6 GHz for fifth-generation (5G) wireless communications. Three well-known path loss models are compared for single-frequency and multi-frequency schemes: the close-in (CI) free space reference distance model, the floating intercept model (FI), and the alpha-beta-gamma (ABG) model. This paper also proposes a new path loss model to account for frequency attenuation (FA) with distance, which we term the FA path loss model. In this model, we introduce a frequency-dependent attenuation factor XF(f), which directly adds to the CI reference attenuation. Ultra-wideband measurements are conducted for different frequencies in the range of 10–40 GHz in an outdoor environment for line-of-sight scenarios. The time dispersion parameters mean excess delay, root mean square delay spread (RMS-DS), and maximum excess delay are estimated. The results reveal that the path loss exponent values for CI models are less than 1.4 in our experimental set-up. For the proposed FA model, with a path loss exponent of 1.4, the XF(f) attenuation factor values are less than 9.7 dB. The time dispersion findings from this work reveal that the RMS-DS values varied between 0.1 and 1.7 ns.